Pengaruh Struktur Modal dan Profitabilitas terhadap Nilai Perusahaan pada Sektor Logam dan Sejenisnya Tahun 2017-2021 - Ahmad Nufyar; Erly Mulyani (Universitas Negeri Padang, 2023)
This study aims to determine the effect of capital structure and profitability on firm value in metal sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The study is a causal study that uses linear regression analysis to test the hypotheses that are asked. The population in this study is the entire metal company and the like listed in the Indonesia stock exchange, which includes 14 companies. The sample retrieval technique used is an purposive sample so that the number of samples used in this study is 70. The source of data used in this study is the data source that is available after it has been collected by others. The research suggests that capital structures have no significant impact on firm values and profitability demonstrate a positive and significant impact on firm values. For further research it is hoped to examine other variables other than capital structures and profitability, and it is hoped that they will multiply samples that will be studied to improve results.